Certification for Teachers and Lecturers and Its Implications For Staff Development - Madya, Suwarsih (English Education Department, Universitas Islam Indonesia, 2007)
The improvement of quality and relevancy,of education with the societal needs has been one of the big educational issues in Indonesia. It has been one of the considerations for the decision to adopt Education Act No. 20/2003 on National Education System. With its quality being improved, education will fulfill well its function, which is